Solubilized β-Glucan Supplementation in C57BL/6J Mice Dams Augments Neurodevelopment and Cognition in the Offspring Driven by Gut Microbiome Remodeling - Dorsilla A. Katimbwa; Yoonsu Kim; Min Jeong Kim; Minsoo Jeong; Jinkyu Lim (Foods)
A maternal diet rich in dietary fiber, such as β-glucan, plays a crucial role in the offspring’s acquisition of gut microbiota and the subsequent shaping of its microbiome profile and metabolome. This in turn has been shown to aid in neurodevelopmental processes, including early microglial maturation and immunomodulation via metabolites like short chain fatty acids (SCFAs). This study aimed to investigate the effects of oat β-glucan supplementation, solubilized by citric acid hydrolysis, from gestation to adulthood. Female C57BL/6J mice were orally supplemented with soluble oat β-glucan (ObG) or carboxymethyl cellulose (CMC) via drinking water at 200 mg/kg body weight during breeding while the control group received 50 mg/kg body weight of carboxymethyl cellulose. ObG supplementation increased butyrate production in the guts of both dams and 4-week-old pups, attributing to alterations in the gut microbiota profile. One-week-old pups from the ObG group showed increased neurodevelopmental markers similar to four-week-old pups that also exhibited alterations in serum markers of metabolism and anti-inflammatory cytokines. Notably, at 8 weeks, ObG-supplemented pups exhibited the highest levels of spatial memory and cognition compared to the control and CMC groups. These findings suggest a potential enhancement of neonatal neurodevelopment via shaping of early-life gut microbiome profile, and the subsequent increased later-life cognitive function.